PERAN MEDIA DIORAMA DALAM MENINGKATKAN PEMBELAJARAN SKI PADA SISWA MI/SD: STUDI PUSTAKA - Oktaviona, Atika Devi; Lestari, Nur Indah; Halimatusya'diyah, Ayu; Azzahra, Eqit Meiliani; Hapsari, Dini Riska; Ghozi, Bagas Abu; Destia, Oleanda Eka; Rif'iyati, Dian (STKIP Subang, 2026)
The teaching of Islamic Cultural History (SKI) in elementary madrasahs is often considered monotonous and difficult to understand due to its abstract subject matter and teaching methods that tend to rely on rote memorization. This study aims to examine the role of dioramas in improving the quality of SKI instruction for elementary madrasah and elementary school students through a concrete visual approach. The method used was descriptive qualitative research involving a literature review, analyzing various scientific publications from 2016–2026 sourced from the Google Scholar, Garuda, DOAJ, and Scopus databases. The results of the study indicate that diorama media can present historical events in the form of concrete three-dimensional visuals, thereby making it easier for students at the concrete operational stage to understand the material. The use of dioramas has been proven to significantly increase students’ motivation, engagement, storytelling skills, and learning outcomes compared to conventional methods. The conclusion of this study affirms that diorama media is an effective innovative alternative for creating interactive and meaningful learning. Theoretically, this study contributes to the development of visual-based learning media in religious education, and practically provides strategic references for educators to address learning fatigue and improve the quality of SKI instruction at the elementary education level.